EVIDENCE OF THE EDGE EFFECT IN ANFHIBIANS OF THE PUCACURO NATIONAL RESERVE, NORTH OF THE PERUVIAN AMAZON - ROJAS ZAMORA, Rommel Roberto (2018)
Amphibians are organisms that have a sensitive relationship to the degradation of habitats and are used as habitat indicators. In this work we use preliminary data from a rapid assessment in the Pucacuro national reserve, Peru to test the influence of the edge effect on amphibians and identify potential habitat indicator species. We calculated and statistically compared the abundance, richness, sizes and spatial fluctuations in amphibian species of 3 sampling zones in 3 distances (Borde, 100 and 200 meters) of deforested areas. Our results suggest the existence of differences in abundance, richness and spatial fluctuations of amphibians in relation to distances and suggest edge effect at least 100 meters from deforested area. As potential habitat indicator were identified Rhinella margaritifera, Chiasmocleis bassleri and species of Pristimantis. Despite being a rapid assessment, our data suggest a strong tendency for spatial changes in abundance of amphibians at different distances from a deforested area.